Contact between Garnet-Type Solid Electrolyte and Lithium Metal Anode: Influence on Charge Transfer Resistance and Short Circuit Prevention. Issue 4 (1st January 2017) - Basappa, Rajendra Hongahally; Ito, Tomoko; Yamada, Hirotoshi
Abstract : Interface structure between Li and garnet-type Li6.5 La3 Zr1.5 Ta0.5 O12 (LLZT) solid electrolyte was investigated by means of electrochemical impedance spectroscopy (EIS) on symmetric cells of Li | LLZT | Li. Charge transfer resistance ( R CT ) between Li and LLZT was investigated using LLZT pellets with various roughness. R CT and activation energy ( E a ) obtained on the flat interface is as high as 746 Ω cm 2 and 0.51 eV at 25°C, respectively, indicating that the charge transfer reaction at Li | LLZT (grit number: #8000) interface is a kinetically slow process, which may suppress rate capability of all solid-state batteries. Although the lowest R CT of 363 Ω cm 2 was obtained by heating up to the melting point of Li for the LLZT pellet polished with an emery paper (#400), it is supposed that electrochemically effective contact area was saturated for rougher surfaces of LLZT. To prepare interfaces with large effective contact area, Li electrodes were deposited on a LLZT pellet by vacuum-evaporation, which exhibited further low R CT of 69 Ω cm 2 . The interface with large effective contact area is also a key to prevention of short circuit, and a high critical current density of 0.4 mA cm −2 was demonstrated.